Scanning electron microscopic study of cold-stored small bowel: comparison of Euro-Collins and Lactated Ringer solutions - (:unkn) unknown (Found Adv Med Sci Inc, Mahwah, NJ, United States, 2000)
A study was carried out to investigate time-related morphological changes of the rat small bowel during preservation of the organ in hypothermic Euro-Collins and Lactated Ringer solutions. Small bowels were perfused via the ascending aorta. After flushing of the intestinal lumen with cold saline solution, perfused grafts were placed in respective preservation solutions at 4°C for 0, 3, 6 and 12 hours. Perfusion and storage in saline solution at 4°C was performed for controls. Biopsy samples were prepared for examination at the light and scanning electron microscopic levels. The results indicate that both preservation solutions are suitable for short term preservation of the small bowel.